2020
DOI: 10.1111/jfpe.13378
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of different Longjing fresh tea varieties using hyperspectral imaging technology and chemometrics

Abstract: Hyperspectral imaging technology was applied to detect and recognize six different varieties of Longjing fresh tea. The data contained image and spectral information at 370–1042 nm; color and texture features were the foci of the image research. Spectral pre‐processing was performed by multiplicative scatter correction (MSC) and standard normal variate (SNV), and then, we selected the corresponding position variable and vegetation indexes as spectral features. Representative features including the most informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Pre-processing techniques have been proposed for reducing noise or modifying the base and slope shift from spectral data, and some previous studies showed that they could sharpen the peaks and valleys of spectra [57,58]. Thus, applying pre-processing transformations was considered to enhance the more chemically relevant peaks and reduce the effects of baseline shifts and overall curvature over the original reflectance (OR).…”
Section: Pre-processing Of the Raw Reflectance Datamentioning
confidence: 99%
“…Pre-processing techniques have been proposed for reducing noise or modifying the base and slope shift from spectral data, and some previous studies showed that they could sharpen the peaks and valleys of spectra [57,58]. Thus, applying pre-processing transformations was considered to enhance the more chemically relevant peaks and reduce the effects of baseline shifts and overall curvature over the original reflectance (OR).…”
Section: Pre-processing Of the Raw Reflectance Datamentioning
confidence: 99%
“…Various studies using near-infrared spectroscopy and hyperspectral imaging to identify tea varieties and geographical origins have been reported. Yan et al [28] used hyperspectral imaging (spectral range: 370-1042 nm) to classify six different varieties of Loingjing fresh tea. The classification accuracy could reach over 94%.…”
Section: Calibration Setmentioning
confidence: 99%
“…Convolutional neural networks, as an important member of image classification algorithms, have the advantages of high recognition accuracy, fast detection speed, and great development potential [ 12 ], have achieved considerable success in image classification [ 13 ], object detection [ 14 ], pose estimation [ 15 ], image segmentation [ 16 ], and face recognition [ 17 , 18 ], have great scaling advantages [ 19 ], and have been widely used in agriculture [ 20 ], healthcare [ 21 ], education [ 22 ], energy [ 23 ], industrial inspection [ 24 ], and other fields [ 25 ]. Currently, convolutional neural networks have been used for tea tree pest and disease identification [ 26 ], tea grade sieving [ 7 ], and the sorting of tea tree fresh leaves [ 8 ], but for the recognition and classification of different species of green tea based on ResNet, a typical convolutional neural network is proposed by researchers in recent years to perform computer vision tasks, which minimizes the gradient disappearance problem caused by increasing the depth of the network due to the introduction of the residual module and reduces the redundancy of information in the data while maintaining a high accuracy rate, which is simple and practical.…”
Section: Introductionmentioning
confidence: 99%